ELT IN KOREA: ENGLISH AS A COMPULSORY SUBJECT IN ELEMENTARY SCHOOL AND ITS CHALLENGES - Shofiya, Arina (Jurnal Bahasa Lingua Scientia, 2011)
As the impact of colonization, the teaching of English in Korea experiences some ups and downs. During Japan colonization, the teaching of English was discouraged, even there was an effort to annihilate English from Korea. After the liberation, the teaching of English was started again for a purpose of maintaining international relationship. To foster people?s capability of English, the Korean government has placed English as a compulsory subject in elementary school starting at Grade 3 to Grade 6 under the Seventh Curriculum Reform in 1997. Such policy leads to some pros and contras among English practitioners. This paper discusses three different opinions from three different writers whose recommendations of such issues are related to each other. First, it presents briefly the writers? opinions about the policy of implementing English education in elementary schools in Korea. Second, it discusses the writers? recommendations related to the unsolved issue. Eventually, the conclusion is taken based on the discussion and presented in the form of summary.